EFL Students' Perceptions on Watching English Movies as Audio-Visual Media to Improve Student’s Vocabulary Mastery - Mubarokah, Evi Nurul; Rizal, Daviq (JETLEE : Journal of English Language Teaching, Linguistics, and Literature, 2025)
This research aims to find out how EFL students' perceptions of watching English movies as audio-visual learning media to improve student’s vocabulary mastery. This study uses a quantitative method, which collects data through questionnaires distributed to 106 students majoring in English education at Walisongo State Islamic University in academic years 2022-2023. The results showed that the majority of students agreed that watching English movies is an effective and fun way to learn English. Students also agree that watching movies helps improve their skills in English including improving their vocabulary. In addition, watching movies helps improve their speaking, listening, reading, writing, pronunciation, as well as increase their understanding of the foreign culture and history they are studying. These results show that movies are an effective learning media for learning English in higher education.